The Effect of Weeding and Planting Distance on Growth and Production of Shallots (Allium Cepa.L) - Achmad Ardi Septian; Agus Miftakhurrohmat (Nabatia, 2019)
This research aims to know the influence of the large number of weeding and planting distance towards the growth and production of onion (Allium we have load. L), was held in the village of Jiken Sub Sidoarjo Reinforcement in January to March 2019. The experiment was devised in factorial using random design group with two factors and repeated 3 times the first Factor is the large number of weeding which consists of 1x(P1), 2x(P2), 3 (P3). The second factor that is a distance of planting that consists of 10 x 10 cm(J1), 10x15 cm(J2), 10x20 cm(J3). The observed variable is the length of the plant, the amount of leaves, the diameter of the tuber, tuber perrumpun amount, the weight of the wet perrumpun, wet weight per hide, dry weight per clump, dry weight per hide, and harvest index. The results of the analysis show the multiplicity of treatment between weeding and planting distance treatment happens different real interaction on variable dry weight per plant, dry weight per hide, and harvest index. Treatment of large number of weeding 1x(P1) with planting distance 10 x 15 cm(J2) produces the most weight (1399.87 gr).